THE INDIGENOUS LEGACY OF THE IEPE MUNICIPALITY, SP: PROTECTION, DISSEMINATION AND MANAGEMENT OF ITS ARCHAEOLOGICAL SITES - Montardy, Lisandra Hernandez [UNESP]; Faccio, Neide Barroca [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2019)
This article reflects on the indigenous legacy of the Municipality of Iepe considering the processes of protection, dissemination and management of its archaeological sites, as well as the creation of the Museum of Archeology of Iepe as an expression of the interest of the local population and the Municipality of Iepe to expand respect for this heritage through its knowledge and appreciation. In the same one the actions of patrimonial education developed in the municipality within the frame of the projects of university extension of the Faculty of Sciences and Technology of the State University Paulista Julio de Mesquita Filho Campus of Presidente Prudente: Museum/University: the extroversion of the knowledge and Prehistory counted through objects. Reflecting on the importance of the patrimonial education program carried out in this context and its focus on sensitization in the school scope of elementary and secondary education of students and teachers with the archaeological riches and the indigenous memory of the West Paulista, promoting the popularization of this knowledge as part strengthening the feelings of identity of the region's population.
Keywords: Municipality of Iepe; MAI; Archaeological heritage; Heritage education